Neoendogenous development in European rural areas. Results and lessons. - (:unkn) unknown (Springer, 2020)
This book is one of the main outcomes of the projects “Development Programmes and Rural Change in the European Union: governance, results and lessons to share”and “Successes and failures in the practice of neoendogenous rural development in the European Union (1991-2013)”, funded both of them by the Spanish Ministry of Economy and Competitiveness. This publication aims, on one side, to clarify and deepen the knowledge of the social, economic and territorial effects of the LEADER approach, and, on the other, to analyze the importante of the participation of several stakeholders (young people and women) as well as some traditional activities – agriculture - or modern ones (tourism) linked all of them to the rich cultural and natural heritage of these areas. It also provides an in-depth study of the causes that lead to the generation of successful projects in the practice of neoendogenous rural development and also explores the reasons that cause certain projects to fail in the path towards LEADER support so that they are finally not implemented. In addition, it is shown the problems, results and best practices that cause the neoendogenous rural development in different areas inside of the European Union: Austria, Finland, France, Germany, Italy, Spain and United Kingdom. Thereby it helps to improve the decision-making in rural development, both on a local and regional scale. The multidisciplinary and international character of the authors, as well as the specificity of the research trajectory of each of them, in the analysis of rural development, enriches the publication and facilitates the different and critical reflections on the contributions, errors and meaning of the neoendogenous local development. Researchers in this discipline and technicians working in the practice of rural development along the European Union are the main audience of the book.
Keywords: Ländlicher Raum; Ländliche Entwicklung; Endogene Entwicklung; EU-Programm; Evaluation; Partizipation; Regionalvergleich; Internationaler Vergleich